Investigation On Facile Synthesis Of YAG:Ce Nanoceramic Powder Prepared With Microwave Solution Combustion And Application In White Light Emission - Khai, Shenn Lau; Hassan, Zainuriah; Way, Foong Lim; Hock, Jin Quah (2020)
Cerium doped yttrium aluminum garnet (YAG:Ce) phosphor was widely used as color converter in white light emitting diode (wLED). Such phosphor was commonly synthesized with high temperature solid-state reaction. However, powder derived from this method exhibited irregular and highly agglomerate particles. A repeated milling process to break the particles will cause additional defects formation, causing the optical properties to deteriorate. In this work, YAG doped with 0.1 mol% of cerium nanoceramic powder has been synthesized with facile mixed-fuel microwave solution combustion synthesis (MSCS). The as-synthesized powder was subjected to a post-annealing treatment to enhance the structural and optical properties. HR-XRD revealed an increased in crystallinity as well as crystallite size for the annealed powder. Moreover, FESEM analysis showed spherical-like nanoparticles morphology. For optical properties, broad yellow emission centered at 534 nm was demonstrated with PL measurement. Finally, the YAG:Ce phosphors was fabricated into wLED and characterized with electroluminescence (EL) measurement to determine the color properties (CIE, CCT and CRI).